Histopathological Spectrum of Gastroduodenal Biopsies in North East India - A 1 Year Cross-sectional Study in a Tertiary Care Centre - Sarma, Usha; Kalita, Upasana (Asian Pacific Journal of Cancer Biology, 2024)
Background: Gastrointestinal problems are very common nowadays and most people are likely to experience gastrointestinal symptoms throughout their lives. Acid peptic disease (APD), including gastric ulcers, duodenal ulcers, and gastro esophageal reflux disease is a common disorder of the gastrointestinal region, the pathogenesis of which involves an imbalance between acid secretion and gastric mucosal defenses. Besides, malignancies are also fairly common in these regions. This is a study done in 100 cases of gastroduodenal biopsies in a 1 year period. Aims and Objectives: To see the histopathological spectrum of gastro-duodenal biopsy tissue collected by endoscopy and to correlate the association with clinical and demographic findings. Result: The prevalence of gastroduodenal lesion is more common among males around the fifth decade of life. Abdominal pain and dyspepsia were the most common presenting clinical complaint. There were 56 benign cases, 11 cases of premalignant category (Dysplasia/ Metaplasia) and 27 malignant cases, out of which Moderately differentiated Adenocarcinoma was the most common. Conclusion: Endoscopic gastroduodenal biopsies helps in detecting benign as well as malignant lesions. A variety of non-neoplastic and neoplastic lesions were reported in the present study across a wide range of age and site distribution. The combination of endoscopy and histopathological study of gastroduodenal biopsy provide a powerful diagnostic tool for better management of patients.